2010
DOI: 10.1007/s00128-010-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Levels of PCDD/Fs in Agricultural Soils near Two Municipal Waste Incinerators in Shanghai, China

Abstract: A study was conducted on polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/F) in agricultural soils at 41 sites within a radius of 3 km from two municipal solid waste incinerators in Shanghai. The PCDD/F concentrations ranged from 71.32 to 3,881.44 pg g⁻¹ (0.64-61.15 pg I-TEQ g⁻¹). The highest PCDD/F concentrations were found approximately 1,000 m from the municipal solid waste incinerators. The PCDD/F homologue profiles of all soil samples were compared with the profiles from suspected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…In general terms, the current levels of PCDD/ Fs in soils were lower than those in other studies near MSWIs. Deng reported a range of concentrations between 0.640 and 64.2 pg I-TEQ/g in the vicinity of a MSWI in Shanghai (China), whereas in Taiwan the levels ranged between 0.850 and 4.50 pg I-TEQ/g (Deng et al, 2011;Chen et al, 2011). The levels in our current study were also lower than for other types of soil reported by Nadal and Turgut (Nadal et al, 2009;Turgut et al, 2012).…”
Section: Levels and Profiles Of Pcdd/fs In Soil Samplescontrasting
confidence: 75%
“…In general terms, the current levels of PCDD/ Fs in soils were lower than those in other studies near MSWIs. Deng reported a range of concentrations between 0.640 and 64.2 pg I-TEQ/g in the vicinity of a MSWI in Shanghai (China), whereas in Taiwan the levels ranged between 0.850 and 4.50 pg I-TEQ/g (Deng et al, 2011;Chen et al, 2011). The levels in our current study were also lower than for other types of soil reported by Nadal and Turgut (Nadal et al, 2009;Turgut et al, 2012).…”
Section: Levels and Profiles Of Pcdd/fs In Soil Samplescontrasting
confidence: 75%
“…To better compare the results with available data, the total dioxins I-TEQ concentrations in soils are summarized in Figure 4. For MSW incinerator emission sources (see Figure 4A), the total I-TEQ values in soils near the studied MSW incinerator are close to or smaller than that in most other studies, such as the research focused on Beijing (Li W. et al, 2014), Hangzhou (Jin et al, 2012), Shanghai (Deng et al, 2011), Northern Taiwan (Wang et al, 2008) in China and Moscow Parks (Shelepchikov et al, 2011) in Russia. The potential reason might be that the studied MSW incinerator is located in the suburb of Qionghai (a city of Hainan Province), which has the low level of industrialization, and small number of large-scale industrial plants (Xu et al, 2014;Wu et al, 2016), therefore largely reducing the impact of other anthropogenic emission sources on the pollutant concentrations in soils (Guo et al, 2012).…”
Section: Figuresupporting
confidence: 55%
“…In turn, Vilavert et al (2010) reported a mean soil PCDD/F concentration of 0.75 ng I-TEQ kg −1 near a HWI (Constantí, Catalonia) after 10 years of continuous monitoring. On the other hand, levels ranging 0.16-14 ng I-TEQ kg −1 were observed in an industrial zone of Trondheim (Norway) (Andersson and Ottesen, 2008), while PCDD/F concentrations in agricultural soils surrounding two MSWIs in Shanghai (China) ranged from 0.64 to 61.15 pg I-TEQ g −1 (Deng et al, 2011). PCDD/F concentrations in soils near the MSWI of Tarragona are currently in the low part of the range, in comparison with literature data from industrial and urban zones (Nadal et al, 2011), and more specifically lower than results from other authors for corresponding soils near MSWIs (Kim et al, 2009;Wu et al, 2009).…”
Section: Resultsmentioning
confidence: 99%